Kegagalan Penerapan Prinsip CEDAW oleh India dalam Menangani Kasus Dowry Death - Lisa Cahyanida Siswanto; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2020)
India is one of 189 countries that ratified the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), a convention that protects women's rights. However, the practice of dowry that harms women continues to this day. This practice requires the bride to grant a number of dowry to the groom. Dowry’s request that was not fulfilled prompted the groom’s family to commit acts of violence that could result in bride’s death. This phenomenon has known as dowry death. Hence, this research seeks to prove the reason for the existence of dowry deaths even though India has already ratified CEDAW. This research is a qualitative research that explained through the concept of noncompliance. This research found that the practice of dowry continued to occur due to the lack of optimal implementation of CEDAW by India’s government, NGOs and local communities.